Fabrication and Analysis of Physico-Mechanical Characteristics of Chemically Treated Bhendi Fiber Reinforced Thermoplastic Composites: Effect of UV Radiation - Zaman, Haydar (Malaysian Journal on Composites Science and Manufacturing, 2024)
Unidirectional polypropylene (PP) composites reinforced with bhendi fibers (BFs) were produced after BFs were subjected to UV light at different intensities. Mechanical parameters such as tensile strength, tensile modulus, and impact strength of irradiated BF/PP composites significantly improved compared to non-irradiated counterparts. To enhance their properties, different amounts of 2-hydroxyethyl methacrylate (HEMA) in methanol were applied to the surfaces of irradiated BFs, and UV light was subsequently used to cure them. Tensile strength, tensile modulus, and impact strength values rose by 32%, 20%, and 37%, respectively, after the optimized grafting and mechanical properties. Alkali solutions were applied to BFs for 30 minutes at varying temperatures and concentrations to alter their surfaces. Then, using the same UV light, BFs were photocured after being grafted with an optimal HEMA solution. Of all the composite samples treated with 10% HEMA, the alkali + 10% HEMA-treated composites exhibited superior mechanical performance. SEM studies exhibited that the optimized alkali with 10% HEMA treated composite had better dispersion than the 10% HEMA treated composite. Water absorption was significantly lower in the treated than in the untreated sample. According to weather studies, the treated specimens may have less loss tensile characteristics than the untreated specimens.